PERTUMBUHAN LARVA IKAN BETOK (Anabas testudineus) YANG DIRENDAM DALAM LARUTAN HORMON TIROKSIN DENGAN KONSENTRASI DAN LAMA WAKTU PERENDAMAN YANG BERBEDA - Masyita Pebriyanti; Muslim .; Yulisman . (Jurnal Akuakultur Rawa Indonesia, 2015)
ABSTRACT The problem of development of climbing perch culture was low in growth rate. The effort to increase growth rate of climbing perch is hormonal treatment, including the hormone thyroxine. The aim of this research was to determine the effective consentration and duration of immertion of thyroxine hormone to increase yolk sack absorbtion and growth rate. This research held in August to September 2014 in Laboratorium Dasar Perikanan, Aquculture Study Departement, Faculty of Agriculture, Sriwijaya University, Indralaya. This research using factorial completely rondomezed design with two factors, the first was thyroxine consentration with immersion media (K1=0.01 mg.L-1, K2=0.05 mg.L-1, K3=0.1 mg.L-1) and the second was the long immersion (W1=24 hours, W2=48 hours, W3=72 hours) with three replication. The parameters that observed were yolk sack absorption, growth, survival rate and water quality. The result showed that the highest yolk sack absorbtion was K2 (0.05 mg.L-1) and K3 (0.1 mg.L-1). The highest growth was K3W2 (0.1 mg.L-1 of consentration and immersion for 48 hours) with the weight was 316.1 mg and length was 26.56 mm. The best survival rate was 88.67% (K1W1). The value of water quality during larva rearing were temperature 26-28 oC, pH 5.6-6.5, dissolved oxygen 4.43-5.93 mg.L-1 and ammonia 0.00-0.03 mg.L-1 Â  Keywords : Climbing perch larvae, thyroxine hormone, duration of immertion, growth